Mixed Markov models applied for population changes in Spain - Jesus Perez-Mayo; Miguel A. Fajardo (European Regional Science Association (ERSA), 1998)
In this paper, common patterns of transition are tried to find in population. We look for chains in order to group Spanish provinces into clusters. Besides, income changes are analysed by the same procedure. Finally, we combine both studies to compare them Population and income data since 1960 to 1996 are collected form I.N.E. (National Spanish Institute of Statistics) databases.
Keywords: 330